Coaching a kultura narcyzmu = Coaching and the culture of narcissism - Francuz, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Coaching often goes hand in hand with positive thinking and fits in with a modern culture that promotes individuals donning the shiny masks of happy successful people who fulfil their potential by pursuing their plans and dreams. It combines with habitual optimism, with exposing only the good, bright sides of life. In this way, coaching supports the so-called culture of narcissism.
Keywords: coaching; narcyzm; coaching transpersonalny; Ja-Ty; Ja-Ono; duchowość; Buber, Martin (austriacki filozof; 1878-1965); narcissism; transpersonal coaching; spirituality; I-Thou; I-It